Bimetallic nanoparticles supported ionic liquid as an effective heterogeneous nanocatalyst for green synthesis of chromenes under solvent‐free conditions. (9th October 2022) - Kazempour, Somayeh; Naeimi, Hossein
Abstract : In this research, a novel bimetallic nanoparticles supported by 1, 3‐bis (triethoxysilylpropyl) imidazolium hydrogen sulfate ionic liquid (Ni.Cu@SiO2 .BSPIm/HSO4 ) are designed and prepared, and its catalytic activity is investigated in organic reaction. The prepared nanocatalyst was characterized using Fourier‐transform infrared spectroscopy (FT‐IR), energy‐dispersive X‐ray, thermogravimetric analysis, field emission scanning electron microscopy, and X‐ray powder diffraction techniques. This catalyst exhibited great activity in the one‐pot synthesis of chromene derivatives through condensation reaction. The products were obtained with high purity in high to excellent yields and short reaction times. The organic products were identified by melting points, FT‐IR, and 1 H NMR analyses. Abstract : In this research, a novel bimetallic nanoparticles supported by 1, 3‐bis(triethoxysilylpropyl) imidazolium hydrogen sulfate ionic liquid (Ni.Cu@SiO2.BSPIm/HSO4) are designed and prepared, and its catalytic activity is investigated in organic reaction.